Potential Infectious Etiology of Behçet's Disease. (29th December 2011) - Galeone, Massimiliano; Colucci, Roberta; D'Erme, Angelo Massimiliano; Moretti, Silvia; Lotti, Torello
Abstract : Behçet's disease is a multisystem inflammatory disorder characterized by recurrent oral aphthous ulcers, genital ulcers, uveitis, and skin lesions. The cause of Behçet's disease remains unknown, but epidemiologic findings suggest that an autoimmune process is triggered by an environmental agent in a genetically predisposed individual. An infectious agent could operate through molecular mimicry, and subsequently the disease could be perpetuated by an abnormal immune response to an autoantigen in the absence of ongoing infection. Potentia bacterial are Saccharomyces cerevisiae, mycobacteria, Borrelia burgdorferi, Helicobacter pylori, Escherichia coli, Staphylococcus aureus, and Mycoplasma fermentans, but the most commonly investigated microorganism is Streptococcus sanguinis. The relationship between streptococcal infections and Behçet's disease is suggested by clinical observations that an unhygienic oral condition is frequently noted in the oral cavity of Behçet's disease patients. Several viral agents, including herpes simplex virus-1, hepatitis C virus, parvovirus B19, cytomegalovirus, Epstein-Barr virus and varicella zoster virus, may also have some role.